The Strategy Development of Tourism in The Kajuik Lake Lagam Subdistrict Pelalawan Regency Riau Province - Noprianty, Widya; Kusai, Kusai; Warningsih, Trisla (Jurnal Perikanan dan Kelautan, 2018)
This research was conducted to identify the exsisting condition of Kajuik lake tourism,to study the development strategy and to find alternative of Kajuik Lake tourism development.The method used in this research is survey method. The results showed that Kajuik Lake has ecotourism potential that is still beautiful, but the facilities and infrastructure in Lake Kajuik have not been adequate, such as the lack of tourism acts and difficult to access Kajuik Lake tour especially during the rainy season beside that, Kecamatan Langgam has traditional cultural tourism destination Balimau kasai potang mogang which is held every year. Based on the analysis of interests (SWOT Analysis) shows that the priority sequence of strategy consists of Development of doing the development of cultural and maritime tourism (ecotourism) with the importance of 2.54, intensifying local tourism promotion with importance value 1.72, supporting facilities and infrastructure of tourism objects with the interests of 0,74